Inheritance in Banjar Customary Law and Islamic Law: a Study of The Status of Children as Recipients of Inheritance - Supiannor, Ahmad (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study presents a comparative analysis between inheritance systems in Banjar customary law and Islamic law, focusing specifically on the status of children as heirs. In Banjar society, not only biological children but also stepchildren, adopted children, and children born out of wedlock (referred to as anak kampang) are potentially entitled to inheritance, often based on family discussions and social-emotional considerations. In contrast, Islamic inheritance law (faraid) only recognizes the right to inherit based on three legal causes: marriage, bloodline (nasab), and wala’ (loyalty through manumission). The study finds that while Banjar inheritance customs may diverge from the strict rules of Islamic law, they can be harmonized through the concept of ihsan, showing kindness to non-heirs, provided all legitimate heirs consent. This research adopts a normative legal method with comparative and conceptual approaches, using secondary data analyzed qualitatively. The findings suggest that harmonization between local custom and Islamic law is possible as long as justice and mutual consent are preserved.